EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura) MENINGKATKAN KETAHANAN MEMBRAN ERITROSIT TIKUS YANG DIPERLAKUKAN DIABETES MELLITUS - Hasan, Fonnie Esther; Gobel, Sri Yunanci Van; Magdalena, Magdalena; Fristiohady, Adryan; Yunus, Reni (Poltekkes Kemenkes Bandung, 2023)
The condition of Diabetes Mellitus (DM) due to hyperglycaemia can induce free radicals and decreased oxidant defence system, chronic hyperglycaemia will result in increased production of free radicals resulting in oxidative stress. The aim of this study was determine the oxidant activity of Kersen Leaf Extract in increasing the resistance of erythrocyte membranes in rats treated with diabetes mellitus by measuring the activity of Malondialdehyde (MDA) and measuring the percentage of erythrocyte cells that are hemolyzed. This study was conducted in vivo by examining the antioxidant activity of Muntingia calabura L. by measuring the levels of MDA and membrane resistance in diabetic rats. This study used animal model Rattus Norvegicus Wistar strain, total of 30 rats was divided into six groups with 5 rats in each group, which are negative control group, positive control group, positive control was added standard drug group, and diabetic rats. Kersen (Muntingia calabura L.) leaves extract reduced Malondialdehyde (MDA) levels of erythrocytes in diabetic rats at an optimum dose of 400 mg/kg of weight per day with a mean MDA value of 4.91 ± 2.1 µmol/ml. In addition, can reduce the amount of hemolysis of erythrocytes in diabetic rats at an optimum dose of 400 mg/kg of weight per day, and can reduce the number of abnormal erythrocytes in rats treated with diabetes mellitus with an optimum dose of 400 mg/kg bw/day with a mean haemolysis value of 33.34 ± 4.04%. Kersen (Muntingia calabura L) leaf extract increases the resistance of erythrocyte of diabetic rat’s.